FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY YANG DIMODERASI OLEH PROFITABILITAS PADA PERUSAHAAN SUBMANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2013-2017 - Amelia, Devina Rizki; Chomsatu, Yuli; Masitoh, Endang (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
The aim of this research is to This study aims to determine the factors that influence audit delay which are moderated by profitability in automotive and component manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017. The method of determining the sample uses purposive sampling with a total sample of 35 financial statements. Data analysis techniques using linear regression analysis moderation. The results of the tests show that the size of the company, auditor opinion, KAP size, operating profit and loss and profitability do not affect audit delay while leverage affects audit delay. Company size, auditor opinion, KAP size, operating profit and loss that profitability is able to moderate (weaken) on audit delay while leverage that profitability is able to moderate (increase) in audit delay.